Dakwah Bil-Qashas: Analisis Metode Dakwah pada Buku The Untold Islamic History 2 Karya Edgar Hamas - Ramadhani, Suci; Padli, Ruslan (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2023)
ABSTRACTDa'wah through the example of stories has now become one of the da'wah that can be considered effective for da'wah partners. So, this article was written to analyze the bil-qashas da'wah approach and analyze the da'wah methods found in the book The Untold Islamic History 2 by Edgar Hamas. The type used in this research uses a descriptive qualitative approach by presenting data analysis in the form of sentences. The data used in this research is in the form of books, journals, and writings that support the research. The results of the study answered that the da'wah method in the book The Untold Islamic History 2 by Edgar Hamas uses the bil-qashas da'wah approach, namely conveying da'wah messages through inspiring stories of Muslim figures by the da'wah method based on the Al-Qur'an, conveying stories in a wise manner (hikmah), mau'izhah hasanah (good teaching), and mujadalah(debating) in a good way.